Factors associated with drug use in prison - results from the Norwegian offender mental health and addiction (NorMA) study - Anne Bukten; Ingunn Olea Lund; Stuart A. Kinner; Eline Borger Rognli; Ingrid Amalia Havnes; Ashley Elizabeth Muller; Marianne Riksheim Stavseth (BMC, 2020)
Abstract Background Remarkably little is known about drug use during imprisonment, including whether it represents a continuation of pre-incarceration drug use, or whether prison is also a setting for drug use initiation. This paper aims to describe drug use among people in prison in Norway and investigate risk factors associated with in-prison drug use. Methods We used data from the Norwegian Offender Mental Health and Addiction (NorMA) Study, a cross-sectional survey of 1499 individuals in Norwegian prisons. Respondents reported on drug use (narcotics and non-prescribed medications) both before and during imprisonment. We used multivariate logistic regression to investigate the associations between drug use in prison and demographics, previous drug use, mental health, and criminal activity. Results Sixty-five percent of respondents reported lifetime drug use, and about 50% reported daily use of drugs during the 6 months before incarceration. Thirty-five percent reported ever using drugs in prison, but initiation of drug used during incarceration was uncommon. In a multivariate model, factors independently associated with drug use in prison included lifetime number of drugs used (adjusted odds ratio [aOR] = 1.17; 95% confidence interval [CI] 1.12-1.23; p <  0.001), daily drug use in the 6 months before imprisonment (aOR = 7.12; 95%CI 3.99-12.70; p <  0.001), and being intoxicated while committing the crime related to current imprisonment (aOR = 2.13; 95%CI 1.13-4.03; p = 0.020). Conclusions In-prison drug use is independently associated with high-risk drug use before imprisonment. To reduce drug use in prison, correctional services must systematically screen for pre-prison drug use and offer effective drug treatment for those in need.